2017
DOI: 10.18203/2349-3291.ijcp20173187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactation counselling on breast feeding: randomized control trial

Abstract: Background: Breastfeeding for a newborn is a standard of care. Breast feeding rates are documented low in our country. Objective of present study was to find out the effect of lactation counselling on breast feeding rates.Methods: It was an open lable randomized control trial and conducted at Department of Pediatrics and Obstetrics of a tertiary care hospital of Northern India. Eligible subjects were 3rd trimester mothers admitted for delivery. Student t test and chi square test were used.Results: Breast feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…10 Choudhary R study found that there was significantly early initiation of Breastfeeding in intervention group (those who received Breastfeeding counselling admitted for delivery) than control group (p = 0.0001). 14 Similar results on timing of initiation of Breastfeeding were seen by others. 15,16 Studies reported that early initiation of Breastfeeding had powerful influence over the duration of EBF up to 6 months.…”
Section: Discussionsupporting
confidence: 83%
“…10 Choudhary R study found that there was significantly early initiation of Breastfeeding in intervention group (those who received Breastfeeding counselling admitted for delivery) than control group (p = 0.0001). 14 Similar results on timing of initiation of Breastfeeding were seen by others. 15,16 Studies reported that early initiation of Breastfeeding had powerful influence over the duration of EBF up to 6 months.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, a study of selected Mexican hospitals showed that counseling combined with babies staying with their mothers, significantly increased full breastfeeding among primiparous mothers [10]. Similar results were obtained in study done by Agre et aland Holmes et al [11,12].…”
Section: Discussionsupporting
confidence: 74%
“…The calculated sample size was 188 (94 for each group) and after using a design effect of 1·5 and adding 10 % lost to follow-up, the final sample size was 310 (155 for each group). For the second specific objective, taking 85·5 and 64 % prevalence of exclusive breast-feeding in the intervention group and in the control group, respectively, from a study done in India ( 31 ) . The calculated sample size was 120 (60 for each group) and after using a design effect of 1·5 and adding 10 % lost to follow-up, the final sample size was 198 (99 for each group).…”
Section: Methodsmentioning
confidence: 99%